Strategies of neoadjuvant therapy in esophageal cancer: a study on the effects of treatment frequency and surgery interval - Lv, Huilai; Chen, Bisong; Gai, Chunyue; Liu, Yu; Ding, Weilu; Wang, Mingbo; Sun, Kangbo; Zhang, Fan; Zhu, Yonggang; Li, Zhenhua; Tian, Ziqiang (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant immunochemotherapy has shown remarkable efficacy in locally advanced ESCC. Therapy cycles and interval to surgery impact treatment efficacy. However, no consensus exists on the optimal cycles or surgical timing. This study investigates these factors to optimize perioperative management and improve patient outcomes.MethodsThe postoperative follow-up data of 255 patients with esophageal cancer who were treated in the Department of Thoracic Surgery at the Fourth Hospital of Hebei Medical University from between November 6, 2019, and June 4, 2024, were retrospectively analyzed. A multivariate logistic regression with restricted cubic splines (RCS) was employed to model the association between the interval from treatment to surgery and primary outcomes.ResultsAll patients underwent neoadjuvant chemoimmunotherapy and 105 (41.1%) completed 2 cycles, 113 (44.3%) completed 3 cycles, and 37 (14.5%) completed 4 or more cycles. Most patients had an interval of 5 to 7 weeks between neoadjuvant therapy and surgery, with the highest proportion undergoing surgery at 6 weeks. Two cohorts were stratified by an interval of <6 weeks or ≥ 6 weeks with RCS. The short-interval group exhibited a higher survival probability in OS (P=0.059) and significantly better outcome in terms of DFS (P=0.018). The effect of different treatment cycles on survival outcomes revealed no significant differences in DFS (p=0.19) and OS (P=0.3).ConclusionSurgical interval of less than six weeks following neoadjuvant chemoimmunotherapy is associated with improved disease-free survival and a trend toward better OS. While treatment cycle number exhibited no significant impact on survival. But these findings warrant further validation through multicenter prospective trials.